PRECISION PUBLIC HEALTH PERSPECTIVE: IS GENOMIC POPULATION SCREENING A VIABLE OPTION FOR THE EARLY DETECTION OF RISKS FOR ONCOLOGICAL DISEASES? REFLECTIONS FROM SERBIA - Đikanović, Bosiljka; Janković, Janko; Cavic, Milena (Srpski medicinski časopis Lekarske komore, 2025)
This paper aims to discuss the term precision public health and its application in the early detection of oncological diseases and genomic risks for these diseases. The use of artificial intelligence and genomic profiling are briefly elaborated on, including reflections on the current status of innovative approaches in the Republic of Serbia. An environment for big genetic and health data sets storage that is protected and interoperable needs to be created, in keeping with the findability, accessibility, interoperability, and reusability (FAIR) principles. Wider use of genomics in the early detection of risks for oncological diseases must meet the well-established criteria for population screening, which is currently not the case. The risk factors that can trigger the penetrance of genes, thus leading to oncological disease, are also well known, and are as follows: unhealthy environments including air pollution, smoking and exposure to second-hand smoke, stress, unbalanced diet, and other harmful factors. Therefore, health governance bodies and health policy decision-makers should focus on building a healthy environment as much as on working on the technical and technological health information infrastructure necessary for further development of genomics and precision public health.